KEAJAIBAN ILMIAH AL-QUR’AN: I’JAZ DAN MUKJIZATNYA DALAM KAJIANSAINS MODERN - Anisa Utami Novianty; Nasrullah Bin Sapa, Halimah Basri (CV. Adiba Aisha Amira, 2025)
The article discusses the Qur’an, as the holy book of Muslims, not only has linguistic an spritual miracles, but also contains scientific miracles that are relevant to the development of modern science. I’jaz Al-Qur’an refers to the miracle of the language and structure of the Qur’anic text that cannot be imitated by anyone, while the miracles of the Qur’an include extraordinary aspects that prove the truth of divine revelation. This article aims to examine the relationship between I’jaz and the miracles of the Qur’an, especially in the context of modern science. This study includes a review of various verses of the Qur’an related to natural phenomena, biology, astronomy, and physics. This article shows that the miracles of the Qur’an are not only in the spritual and linguistic dimensions, but are also scientifically proven in the context of modern times. This study reveals that the miracles of the Qur’an have infinite dimensions, which continuously challenge human understanding of the universe and provide stronger evidence of the truth of divine revelation.